Discerning the Surface and Bulk Recombination Kinetics of Organic–Inorganic Halide Perovskite Single Crystals - Wu, Bo (2017)
Organic–inorganic halide perovskite single crystals possess many outstanding properties conducive for photovoltaic and optoelectronic applications. However, a clear photophysics picture is still elusive, particularly, their surface and bulk photophysics are inexorably convoluted by the spectral absorbance, defects, coexisting photoexcited species, etc. In this work, an all-optical study is presented that clearly distinguishes the surface kinetics from those of the bulk in the representative methylammonium-lead bromide (MAPbBr3) and -lead iodide (MAPbI3) single crystals. It is found that the bulk recombination lifetime of the MAPbBr3 single crystal is shortened significantly by approximately one to two orders (i.e., from ≈34 to ≈1 ns) at the surface with a surface recombination velocity of around 6.7 × 103 cm s−1. The surface trap density is estimated to be around 6.0 × 1017 cm−3, which is two orders larger than that of the bulk (5.8 × 1015 cm−3). Correspondingly, the diffusion length of the surface excited species is ≈130–160 nm, which is considerably reduced compared to the bulk value of ≈2.6–4.3 μm. Furthermore, the surface region has a wider bandgap that possibly arises from the strong lattice deformation. The findings provide new insights into the intrinsic photophysics essential for single crystal perovskite photovoltaics and optoelectronic devices.